Impoliteness Strategies Used by the Baroness in the Movie Cruella - Alicia Tandiono; Nani Indrajani Tjitrakusuma (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
This study aims to find out the types of impoliteness strategies and the similarities and differences of the impoliteness strategies used by the Baroness, an antagonistic character with an impressive background, toward Estella and Cruella in the movie Cruella. The theoretical framework used is Culpeper’s (1996, 2005) and Bousfield’s (2008) impoliteness strategy. This study employed a qualitative approach. The writers collected and analyzed the Baroness’ utterances to her subordinate, Estella, and to her business rival, Cruella, during the business scenes. The Baroness used all six types of impoliteness strategies to Estella, namely: bald on record impoliteness, positive impoliteness, negative impoliteness, sarcasm/mock politeness, withhold politeness, and off-record impoliteness. On the contrary, the Baroness only used four out of six types of impoliteness strategies to Cruella, specifically excluding: negative impoliteness and withhold politeness. The Baroness’ background and personality, as well as the interlocutor’s own background, might have influenced the findings of the study.